Activated carbon hydrogen-rich sheet and preparation method thereof
By using activated carbon hydrogen-rich sheets, the problem of pollutants and heavy metals exceeding the standard when existing hydrogen-rich products electrolyze water, and the effect of improving the taste and safety of electrolyte water is achieved.
Patent Information
- Application Number
- CN202411607774.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing hydrogen-rich products have problems with pollutants and heavy metals when electrolyzing water, which affects the safety and taste of drinking water.
Activated carbon hydrogen-rich sheet is used, which consists of activated carbon, alumina, cellulose, mold release agent and dry binder. By accurately controlling the iodine value and ratio of activated carbon, the odor in water is removed and heavy metal precipitation is avoided.
It improves the drinking taste and safety of electrolytic water, and ensures the purity and safety of water quality.
Smart Images

Figure CN119390175A_ABST
Abstract
Description
Technical Field
[0001] The present invention mainly relates to the technical field of hydrogen-rich sheets, and in particular to an activated carbon hydrogen-rich sheet and a preparation method thereof. Background Art
[0002] Currently, hydrogen-rich products on the market generally use electrolysis to produce hydrogen and oxygen, and can only be used for electrolysis of pure water. The electrolysis operation of mineral water or tap water will lead to the presence of pollutants in the electrolyzed water, affecting the drinking taste; or use mineral hydrogen-rich balls to achieve water electrolysis, but there will be excessive heavy metals, affecting the safety of drinking electrolyzed water. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the prior art. The present invention provides an activated carbon hydrogen-rich sheet and a preparation method. By setting the activated carbon hydrogen-rich sheet, the odor in the water can be removed, and the precipitation of heavy metals in the water can be avoided, thereby improving the drinking taste and safety of electrolyzed water.
[0004] The present invention provides an activated carbon hydrogen-rich sheet, which is configured based on activated carbon, alumina, cellulose, a release agent and a dry binder;
[0005] The activated carbon hydrogen-rich sheet has the following ingredients: 50 parts of activated carbon, 50 parts of aluminum oxide, 5 parts of cellulose, 1 part of a release agent and 3 parts of a dry binder.
[0006] Specifically, the iodine value of the activated carbon is H, and the value range of H is: 1400 mg / g≤H≤1800 mg / g.
[0007] Furthermore, the cellulose is HPMC cellulose.
[0008] Furthermore, the release agent is a polyether substance.
[0009] The present invention also provides a method for preparing an activated carbon hydrogen-rich sheet, wherein the method is used to prepare the activated carbon hydrogen-rich sheet;
[0010] The preparation method comprises:
[0011] Selecting a plurality of raw material components according to the proportion, and mixing the plurality of raw material components uniformly to obtain a raw material mixed powder;
[0012] Dissolving a preset amount of ceramic in pure water to obtain an initial solution;
[0013] Mixing the raw material mixed powder and the initial solution, and stirring for a first preset time to obtain an initial mixed solution;
[0014] Grinding the initial mixed solution by a grinding machine;
[0015] homogenizing the initial mixed solution after the grinding process to obtain a mother solution;
[0016] After drying the mother liquor, a finished dry powder is obtained based on a dry binder treatment;
[0017] The finished dry powder is compressed to obtain an initial finished product;
[0018] The initial finished product is activated to obtain a finished workpiece.
[0019] Specifically, the method of selecting a plurality of raw material components according to the proportion and uniformly mixing the plurality of raw material components to obtain the raw material mixed powder includes:
[0020] 25 kg of activated carbon, 25 kg of aluminum oxide and 2.5 kg of cellulose were selected, and the activated carbon, the aluminum oxide and the cellulose were stirred and mixed to obtain a raw material mixed powder.
[0021] Specifically, the operation of obtaining 25 kg of alumina includes:
[0022] Obtain 15 kg of alumina through a molecular sieve with a silicon-aluminum ratio greater than 800;
[0023] 10 kg of alumina was obtained by passing through a molecular sieve having a silicon-aluminum ratio of 1200.
[0024] Specifically, the raw material mixed powder and the initial solution are mixed and stirred for a first preset time to obtain the initial mixed solution, including:
[0025] The raw material mixed powder and the initial solution are mixed, and the raw material mixed powder and the initial solution are continuously stirred for 30 minutes by a stirrer.
[0026] Further, after drying the mother liquor, obtaining the finished dry powder based on the dry binder treatment includes:
[0027] The mother liquor is heated to 250° C., and the heated mother liquor is dried by hot air to obtain a mother liquor dry powder;
[0028] Add dry binder to the mother liquid dry powder and disperse and mix by high-speed rotation.
[0029] Specifically, the activation of the initial finished product to obtain the finished workpiece includes:
[0030] The initial finished product was dried continuously for 12 hours at an ambient temperature of 120°C;
[0031] The dried finished product is placed in an activation furnace for activation to obtain a finished workpiece.
[0032] The present invention provides an activated carbon hydrogen-rich sheet and a preparation method thereof. By providing the activated carbon hydrogen-rich sheet, odor in water can be removed, and precipitation of heavy metals in water can be avoided, thereby improving the drinking taste and safety of electrolyzed water. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 Schematic diagram of the structure of the activated carbon hydrogen-rich sheet in an embodiment of the present invention;
[0035] Figure 2 It is a schematic diagram of the preparation process of the activated carbon hydrogen-rich sheet in an embodiment of the present invention. DETAILED DESCRIPTION
[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Embodiment 1:
[0038] Figure 1 The schematic diagram of the structure of the activated carbon hydrogen-rich sheet in the embodiment of the present invention is shown. The present invention proposes an activated carbon hydrogen-rich sheet 1, which is composed of activated carbon, alumina, cellulose, a release agent and a dry binder, and the ratio is 50 parts of activated carbon, 50 parts of alumina, 5 parts of cellulose, 1 part of a release agent and 3 parts of a dry binder. As one of the main components, activated carbon has excellent adsorption properties, which can effectively remove impurities and odors in water and ensure the purity of water quality. Alumina has a unique catalytic decomposition effect, which can promote the decomposition of water molecules and produce hydrogen. Cellulose provides the necessary structural support so that the hydrogen-rich sheet 1 can maintain a stable shape. The release agent plays a key role in the manufacturing process, ensuring that the hydrogen-rich sheet 1 is smoothly demolded during the molding process. The dry binder ensures that the components can be tightly combined and improves the overall strength of the hydrogen-rich sheet 1.
[0039] In practical applications, this activated carbon hydrogen-rich sheet 1 has shown excellent performance. When placed in water, the activated carbon begins to absorb impurities and odors in the water, while alumina catalyzes the decomposition of water molecules to produce hydrogen. This process does not require external energy input and can be applied to various types of water sources, including tap water, mineral water, etc. Due to the use of natural and harmless materials, the introduction of harmful substances such as heavy metals is avoided, fundamentally solving the safety problem. At the same time, the purification effect of activated carbon can also improve the taste of water, making hydrogen-rich water more refreshing and delicious.
[0040] The embodiment of the present invention further proposes that the iodine value of the activated carbon in the activated carbon hydrogen-rich sheet 1 is H, and the value range of H is: 1400 mg / g≤H≤1800 mg / g.
[0041] The iodine value of activated carbon is an important indicator to measure its adsorption capacity. The higher the iodine value, the larger the specific surface area of the activated carbon, the more developed the pore structure, and the stronger the adsorption capacity. By controlling the iodine value of activated carbon between 1400mg / g and 1800mg / g, it can be ensured that the activated carbon has a sufficiently large specific surface area and a developed pore structure, thereby improving its adsorption and storage capacity for hydrogen. This technical solution solves the problem of how to improve the performance of activated carbon hydrogen-rich sheet 1 by precisely controlling the iodine value range of activated carbon. A higher iodine value means that the activated carbon has more micropores and mesoporous structures, which provide more adsorption sites for hydrogen molecules. At the same time, the appropriate iodine value range also ensures that the activated carbon will not cause structural instability or excessive preparation cost due to excessively high specific surface area. This optimized activated carbon performance can significantly improve the adsorption capacity and adsorption rate of hydrogen by the hydrogen-rich sheet 1, thereby enhancing its effect as a hydrogen storage medium.
[0042] In the present application, the iodine value of activated carbon can be achieved in the following ways: 1. Raw material selection: Select high-quality raw materials, such as coconut shells, wood or coal, which have a high carbon content and a suitable pore structure, which is conducive to the preparation of activated carbon with a high iodine value. 2. Activation method: Use physical activation or chemical activation methods. Physical activation can be carried out at high temperature using gases such as water vapor and carbon dioxide; chemical activation can use activators such as zinc chloride, phosphoric acid or potassium hydroxide. By adjusting the activation time, temperature and activator concentration, the iodine value can be precisely controlled within the target range. 3. Post-treatment: The prepared activated carbon is subjected to post-treatment processes such as acid washing and heat treatment to further improve and adjust the iodine value.
[0043] There is a close correlation between the iodine value and other characteristics of activated carbon. When activated carbon with a high iodine value is used in combination with alumina, a complementary adsorption system can be formed. Activated carbon is mainly responsible for the physical adsorption of hydrogen, while alumina can further enhance the storage capacity of hydrogen through chemical adsorption. This combination not only improves the overall hydrogen adsorption capacity, but also enhances the adaptability of hydrogen-rich tablets 1 under different temperature and pressure conditions.
[0044] In specific implementation, activated carbon with an iodine value of 1600 mg / g can be selected. This iodine value is in the middle of the recommended range, which can ensure a sufficiently high adsorption capacity without causing structural instability due to an excessively high specific surface area. At the same time, the ratio of activated carbon with this iodine value to 50 parts of aluminum oxide can achieve the best hydrogen adsorption effect.
[0045] The present application effectively solves the problem of how to improve the performance of activated carbon in the activated carbon hydrogen-enriched sheet 1 by controlling the iodine value of the activated carbon. High-iodine-value activated carbon has a more developed pore structure and a larger specific surface area, which directly enhances its adsorption capacity for hydrogen molecules. During the hydrogen enrichment process, high-iodine-value activated carbon can quickly capture and store more hydrogen molecules, thereby improving the overall efficiency of the hydrogen-enriched sheet 1. At the same time, due to the precise control of the iodine value range, the structural stability of the activated carbon is guaranteed, avoiding the problem of structural collapse that may be caused by excessively high specific surface area.
[0046] The present invention further proposes that the cellulose is HPMC cellulose, hydroxypropyl methylcellulose (INN name: Hypromellose), also simplified as hydroxypropyl methylcellulose (abbreviated as HPMC), which is a type of non-ionic cellulose mixed ether.
[0047] As one of the ingredients of activated carbon hydrogen-rich tablets 1, HPMC cellulose plays an important role in the product. HPMC cellulose has good adhesion and film-forming properties, which can help main ingredients such as activated carbon and alumina to better combine together to form a stable sheet structure. At the same time, HPMC cellulose also has certain water absorption and water retention properties, which can adjust the humidity and release rate of the product, which is conducive to the continuous effect of hydrogen enrichment. By selecting HPMC cellulose as the cellulose component of activated carbon hydrogen-rich tablets 1, the structural stability, service life and hydrogen-rich effect of the product can be improved. HPMC cellulose works synergistically with other ingredients such as activated carbon and alumina to form a hydrogen-rich system with excellent performance. This formula design not only solves the problems of product structure and performance, but also improves the overall effect and user experience of hydrogen-rich tablets 1.
[0048] The application of HPMC cellulose in the activated carbon hydrogen-rich sheet 1 can be implemented in a variety of ways. First, HPMC cellulose of different viscosity grades can be selected, such as low viscosity, medium viscosity or high viscosity, to meet different processing and usage requirements. Generally, medium viscosity HPMC cellulose (e.g., 15000-30000 mPa·s) can achieve a good balance between adhesion and processability. Secondly, the amount of HPMC cellulose added can be adjusted according to actual needs, generally between 3-7% of the total formula. 5 parts are selected in this application. This ratio can provide sufficient bonding strength without affecting the performance of other ingredients too much.
[0049] There is an important connection and interaction between HPMC cellulose and activated carbon and alumina. HPMC cellulose forms a mesh structure in the hydrogen-rich sheet 1, encapsulating the activated carbon and alumina particles. This structure not only enhances the mechanical strength of the hydrogen-rich sheet 1, but also controls the penetration rate of water, thereby regulating the hydrogen-rich process. For example, when the hydrogen-rich sheet 1 comes into contact with water, the HPMC cellulose will first absorb water and swell, and then slowly release water. This process can extend the service life of the hydrogen-rich sheet 1 and make the hydrogen-rich effect more lasting. At the same time, the presence of HPMC cellulose can also prevent the loss of activated carbon and alumina particles, maintaining the integrity of the hydrogen-rich sheet 1.
[0050] In practical applications, the selection of HPMC cellulose also needs to consider its dissolution temperature and pH stability. For example, HPMC cellulose with a dissolution temperature of 40-50°C can be selected, so that it will not dissolve when used at room temperature, but can be fully dissolved during the preparation process to play a bonding role. At the same time, selecting HPMC cellulose that is stable in the pH range of 3-11 can ensure the stability of the performance of the hydrogen-rich sheet 1 under different water quality conditions.
[0051] The embodiment of the present invention further proposes that the release agent is a polyether substance.
[0052] Selecting polyether substances as demoulding agents can effectively solve the demoulding problem of activated carbon hydrogen-rich sheets 1 during the preparation process. Polyether substances have good lubricity and release properties, which can reduce the friction and adhesion between the material and the mold during the molding process of activated carbon hydrogen-rich sheets 1, so that the molded product can be demoulded smoothly. The selection of polyether substances as demoulding agents has the following advantages: First, polyether substances have good chemical stability and will not react adversely with other components of activated carbon hydrogen-rich sheets 1, ensuring the quality and performance of the product. Secondly, polyether substances have appropriate viscosity and fluidity, and can be evenly distributed on the surface of the mold to form a thin and uniform demoulding film to ensure the surface quality of activated carbon hydrogen-rich sheets 1. Furthermore, polyether substances are environmentally friendly, safe to use, and meet the environmental protection requirements of modern industrial production. Finally, polyether substances are used in small amounts (only 1 part), which is economical and beneficial, and is conducive to reducing production costs. By using polyether substances as demoulding agents, the production efficiency of activated carbon hydrogen-rich sheets 1 can be significantly improved, the surface quality of the product can be improved, and the performance of the product can be ensured to be unaffected. This selection fully considers many factors such as production process, product quality and economy, and reflects the innovation and practicality of the invention in material selection.
[0053] In the present application, polyether substances can be used as release agents in a variety of specific ways. Common polyether substances include polyethylene glycol (PEG), polypropylene glycol (PPG) and polytetrahydrofuran (PTHF). These substances can be selected and adjusted according to the specific formula and production process of the activated carbon hydrogen-rich sheet 1. For example, PEG with a molecular weight between 200-2000 can be selected, and the selection of the specific molecular weight can be optimized according to parameters such as the molding temperature and pressure of the activated carbon hydrogen-rich sheet 1. For some formulas that require higher temperature molding, PPG can be considered because it has better thermal stability.
[0054] During use, the polyether substance can be directly added to the formula of the activated carbon hydrogen-rich sheet 1, or it can be used as a coating on the mold surface. When used as a formula additive, the addition amount is usually 0.5%-2% of the total formula, and this ratio can be fine-tuned according to actual production conditions. When used as a mold coating, the polyether substance can be dissolved in an appropriate solvent, such as water or ethanol, to make a 5%-10% solution, and then evenly applied to the mold surface.
[0055] The polyether substance as a release agent has a positive interaction with other components of the activated carbon hydrogen-rich sheet 1. It can not only improve the molding effect of the product, but also improve the surface quality of the product. For example, the polyether substance can form a more uniform and stable network structure with cellulose (HPMC), which helps to improve the mechanical strength and durability of the activated carbon hydrogen-rich sheet 1. At the same time, the presence of the polyether substance can also increase the binding force between the activated carbon and the alumina particles, thereby improving the overall performance of the product.
[0056] Embodiment 2:
[0057] Figure 2 A flow chart of a method for preparing an activated carbon hydrogen-rich sheet according to an embodiment of the present invention is shown. The method is used to prepare an activated carbon hydrogen-rich sheet 1 .
[0058] S11: selecting a plurality of raw material components according to a proportion, and uniformly mixing the plurality of raw material components to obtain a raw material mixed powder;
[0059] The preparation method involves multiple technical features, each of which plays an important role in solving the problem of preparing the activated carbon hydrogen-rich sheet 1. The raw material mixing ensures that the components are evenly distributed, laying the foundation for subsequent processing.
[0060] Specifically, several raw material components are selected according to the proportion, and the several raw material components are evenly mixed to obtain the raw material mixed powder, including: selecting 25 kg of activated carbon, 25 kg of aluminum oxide and 2.5 kg of cellulose, and stirring and mixing the activated carbon, aluminum oxide and cellulose to obtain the raw material mixed powder.
[0061] Analysis of technical characteristics: In terms of raw material selection, the selection of three main raw materials, activated carbon, alumina and cellulose, provides the basic materials for the preparation of activated carbon hydrogen-rich tablets 1. In terms of ratio design, the specific ratio design of 25kg activated carbon, 25kg alumina and 2.5kg cellulose ensures the stability of product performance. In terms of stirring and mixing, the three raw materials are fully uniformed through the stirring and mixing process to provide a uniform raw material mixed powder for subsequent processing. This technical solution solves the problems of inaccurate raw material ratio and uneven mixing in the preparation process of activated carbon hydrogen-rich tablets 1 by precisely controlling the raw material ratio and stirring and mixing process. The equal ratio of activated carbon and alumina in the scheme can ensure that the product has good adsorption performance and mechanical strength, and the addition of cellulose helps to improve the molding performance of the product. Through the stirring and mixing process, the components are evenly distributed, laying the foundation for subsequent processing procedures.
[0062] In the present application, the raw material selection can be implemented in a variety of ways. Activated carbon can be selected from activated carbon of different particle sizes, such as 100 mesh, 200 mesh or 300 mesh, to meet different adsorption requirements. Alumina can be selected from γ-alumina or α-alumina, and is selected according to the required specific surface area and porosity. Cellulose can be selected from different types, such as microcrystalline cellulose or carboxymethyl cellulose, to adjust the molding properties and strength of the product.
[0063] In terms of ratio design, the equal ratio of activated carbon and alumina (25kg:25kg) is the result of optimization, which can be fine-tuned in the range of 20kg:30kg to 30kg:20kg to meet different application requirements. The amount of cellulose (2.5kg) can be adjusted in the range of 2% to 5% of the total amount to balance the molding performance and product strength.
[0064] During the mixing process, a high-speed mixer or planetary mixer can be used. The mixing time can be set to 15-30 minutes, and the speed can be adjusted within the range of 200-500rpm to ensure that the raw materials are fully mixed and evenly mixed. The mixing process can be divided into two stages: low-speed premixing and high-speed fine mixing to further improve the mixing uniformity.
[0065] The technical solution of the present application is combined with the preparation method in the preceding claims to ensure the precise proportion and uniform distribution of the components at the raw material mixing stage, laying a good foundation for subsequent solution preparation, grinding, homogenization and other processes. This early stage precise control and the coordination of subsequent processes jointly improve the quality stability and performance consistency of the final product.
[0066] In the technical solution of the present application, the precise proportion and sufficient mixing of activated carbon, alumina and cellulose solve the key problems in the preparation process of activated carbon hydrogen-rich sheet 1. Activated carbon provides a large specific surface area, which enhances the adsorption capacity and hydrogen-rich effect of the product. The addition of alumina improves the mechanical strength and stability of the product, preventing it from breaking or dissolving during use. Cellulose, as a binder, improves the molding properties of the product and also helps to control the dissolution rate of the product.
[0067] The mixing process ensures uniform distribution of the three raw materials, avoiding local aggregation or stratification, which is crucial for the consistency of product performance. Uniform raw material distribution enables subsequent processing steps (such as pressing, activation, etc.) to act evenly on the entire material, thus ensuring the quality stability of the final product.
[0068] This technical solution obtains alumina by using molecular sieves with different silicon-aluminum ratios, and specifically includes two steps: using a molecular sieve with a silicon-aluminum ratio greater than 800 to obtain 15kg of alumina, and using a molecular sieve with a silicon-aluminum ratio of 1200 to obtain 10kg of alumina. This method of using molecular sieves with different silicon-aluminum ratios can obtain alumina with different properties. This technical solution obtains alumina by using two molecular sieves with different silicon-aluminum ratios, which can make the final alumina have better performance. Molecular sieves with higher silicon-aluminum ratios have stronger selectivity and stability, and can obtain alumina with higher purity. By using two molecular sieves with different silicon-aluminum ratios, an alumina raw material with more balanced performance can be obtained, thereby improving the performance and quality of the final activated carbon hydrogen-rich sheet 1.
[0069] In the present application, the process of obtaining alumina can be achieved in a variety of ways. First, for molecular sieves with a silicon-aluminum ratio greater than 800, a molecular sieve with a silicon-aluminum ratio between 800-1000 can be selected, such as a molecular sieve with a silicon-aluminum ratio of 850, 900 or 950. These molecular sieves have high selectivity and stability, and can obtain alumina with higher purity. Secondly, for molecular sieves with a silicon-aluminum ratio of 1200, a molecular sieve with a silicon-aluminum ratio between 1150-1250 can be selected, such as a molecular sieve with a silicon-aluminum ratio of 1180, 1200 or 1220. These molecular sieves have higher selectivity and stability, and can obtain alumina with higher purity.
[0070] The use of two molecular sieves with different silicon-aluminum ratios has important correlations and interactions. The molecular sieve with a silicon-aluminum ratio greater than 800 is used to obtain 15kg of alumina, which has higher purity and stability. The molecular sieve with a silicon-aluminum ratio of 1200 is used to obtain 10kg of alumina, which has higher purity and stability. The combination of the two types of alumina makes the final alumina raw material have more balanced performance, which not only ensures a certain purity, but also takes into account cost-effectiveness.
[0071] In practical applications, the ratio of two molecular sieves to obtain alumina can be adjusted according to specific needs. For example, you can try to use a molecular sieve with a silicon-aluminum ratio of 850 to obtain 16kg of alumina, and use a molecular sieve with a silicon-aluminum ratio of 1200 to obtain 9kg of alumina. This adjustment can be optimized according to actual production needs and raw material performance requirements.
[0072] The present application can effectively solve the problem of obtaining suitable alumina raw materials in the process of preparing activated carbon hydrogen-rich sheets 1 by using two molecular sieves with different silicon-aluminum ratios to obtain alumina. The molecular sieve with a silicon-aluminum ratio greater than 800 is used to obtain 15 kg of alumina, which has high purity and stability and can provide good basic performance for the activated carbon hydrogen-rich sheets 1. The molecular sieve with a silicon-aluminum ratio of 1200 is used to obtain 10 kg of alumina, which has higher purity and stability and can further improve the performance and quality of the activated carbon hydrogen-rich sheets 1.
[0073] The use of two molecular sieves with different silicon-aluminum ratios makes the obtained alumina raw material have more balanced performance. The molecular sieve with a higher silicon-aluminum ratio has stronger selectivity and stability, and can obtain alumina with higher purity. The combination of the two molecular sieves not only ensures the overall purity of the alumina raw material, but also can control the cost to a certain extent. The alumina raw material obtained by this method can significantly improve the performance and quality of the final activated carbon hydrogen-rich sheet 1, so that the hydrogen-rich sheet 1 has better adsorption performance and stability.
[0074] In this regard, the present application further proposes that the operation of obtaining 25 kg of aluminum oxide includes: obtaining 15 kg of aluminum oxide through a molecular sieve with a silicon-aluminum ratio greater than 800; obtaining 10 kg of aluminum oxide through a molecular sieve with a silicon-aluminum ratio of 1200.
[0075] S12: dissolving a preset amount of ceramic in pure water to obtain an initial solution;
[0076] S13: mixing the raw material mixed powder and the initial solution, and stirring for a first preset time to obtain an initial mixed solution;
[0077] That is, a preset amount of ceramic powder is slowly added to a preset volume of pure water, and an initial solution is obtained after stirring and mixing, and a liquid medium is provided for subsequent mixing based on the initial solution.
[0078] Specifically, 1 kg of ceramic powder was slowly added into 10 L of pure water while stirring at a speed of 500 rpm for 30 minutes to obtain an initial solution.
[0079] S14: grinding the initial mixed solution by a grinding machine;
[0080] The raw material mixed powder and the initial solution were added into a planetary mixer and stirred at a speed of 800 rpm for 30 minutes to obtain an initial mixed solution.
[0081] S15: homogenizing the initial mixed solution after the grinding process to obtain a mother solution;
[0082] The initial mixed solution was ground using a horizontal sand mill for 2 hours at a rotation speed of 1200 rpm, and the ground solution was homogenized by a high-pressure homogenizer at a pressure of 100 MPa for 3 times.
[0083] S16: After drying the mother liquor, a finished dry powder is obtained based on a dry binder treatment;
[0084] The raw material mixed powder and the initial solution are mixed, and the raw material mixed powder and the initial solution are continuously stirred for 30 minutes by a stirrer.
[0085] The technical solution achieves full mixing of the raw materials by using a stirrer to continuously stir the raw material mixed powder and the initial solution for 30 minutes. This stirring method can ensure that the various components are evenly distributed and avoid local aggregation or stratification. Continuous stirring for 30 minutes is an optimized time that can fully mix the raw materials without excessive energy consumption or prolonging the production time. This time length is sufficient to break the adsorption force between the particles, so that the different components are fully contacted and mixed, and at the same time, unnecessary physical or chemical changes in certain components will not occur due to excessive stirring. In this way, a uniform initial mixed solution can be obtained, laying the foundation for subsequent grinding, homogenization and other steps. Uniform mixing can improve the quality stability of the final product, ensure the consistency of the performance of each part of the activated carbon hydrogen-rich sheet 1, and improve the overall performance and use effect of the product. In addition, this stirring method is simple to operate, easy to control, and suitable for industrial production. It does not require complex equipment or technology, can reduce production costs, and improve production efficiency. At the same time, since the stirring time is fixed, it is also convenient for standardization and automatic control of the production process.
[0086] In a specific implementation, the agitator can be selected from different types, such as impeller, propeller or turbine agitators. The selection of the appropriate agitator type can be determined based on the physical properties of the raw material mixed powder and the initial solution. For example, for a more viscous mixture, a propeller agitator can be used, which can provide a stronger shear force; for a thinner mixture, an impeller agitator may be more suitable because it can generate a larger fluid circulation.
[0087] The stirring speed is also an important parameter. Generally speaking, the stirring speed can be set between 200-600rpm. A lower speed (200-300rpm) is suitable for the initial stage to avoid splashing of the mixture; it can then be gradually increased to 400-600rpm to ensure adequate mixing. The choice of stirring speed also needs to take into account the viscosity and density of the mixture, as well as the size and shape of the agitator.
[0088] Temperature control is also important during the stirring process. It is usually recommended to stir at room temperature (20-25°C), but appropriate temperature adjustment may be required depending on the characteristics of the specific raw materials. For example, if some ingredients are more easily dissolved or dispersed at higher temperatures, the temperature can be controlled in the range of 30-40°C.
[0089] This technical solution is closely related to the previous steps (such as the selection of raw materials and the preparation of the initial solution). The particle size distribution of the raw material mixture and the concentration of the initial solution directly affect the stirring effect. For example, if the particle size distribution of the raw material mixture is relatively uniform and the concentration of the initial solution is moderate, then a stirring time of 30 minutes is sufficient to achieve the desired mixing effect. On the contrary, if the raw material characteristics are not ideal, it may be necessary to adjust the stirring time or adopt a pretreatment step.
[0090] During the stirring process, an intermittent stirring strategy can be adopted. For example, the stirring can be stopped for 1 minute every 10 minutes, so that the mixture can settle and redisperse naturally in a static state, which helps to break up the local aggregation that may be formed. At the same time, this intermittent stirring can also prevent the temperature increase or degradation of certain ingredients that may be caused by continuous high-speed stirring.
[0091] In order to further improve the mixing uniformity, ultrasonic assisted technology can be used during the stirring process. By installing an ultrasonic generator at the bottom or side wall of the agitator, the cavitation effect of ultrasound can be used to effectively break up the particle agglomeration and promote the uniform dispersion of each component. The use time of ultrasound can be controlled to 1 / 3 to 1 / 2 of the total stirring time, and the power is adjusted according to the volume and characteristics of the mixture, usually between 300-500W.
[0092] In actual operation, the uniformity of the mixture can be observed to determine whether the mixing is sufficient. For example, samples can be taken every 5 minutes during the mixing process. When the uniformity of three consecutive samples does not change significantly, it can be considered that the mixing has reached the ideal state. In addition, the mixing uniformity can also be evaluated by measuring physical parameters such as the viscosity, density or conductivity of the mixture.
[0093] This technical solution effectively solves the problem of uneven mixing of raw material mixed powder and initial solution by precisely controlling the stirring time and method. The 30-minute continuous stirring time is obtained after multiple experimental optimizations. While ensuring adequate mixing, it also avoids the negative effects that may be caused by excessive stirring, such as degradation of certain ingredients or unnecessary energy consumption.
[0094] Uniform mixing sets the stage for subsequent grinding and homogenization. When the initial mixed solution reaches a highly homogenous state, the grinding process can be more efficient because there are no large particle agglomerates to break up. This not only improves grinding efficiency, but also potentially reduces grinding time, thereby reducing energy consumption. Similarly, homogenization becomes easier because the initial state is already fairly homogenous and only further homogenization at the microscopic scale is required.
[0095] In addition, uniform mixing also helps improve the quality stability of the final product. When the components are evenly distributed in the initial stage, the final activated carbon hydrogen-rich sheet 1 will show more consistent performance as a whole. This means that whether it is adsorption capacity, conductivity or mechanical strength, it will maintain a high consistency throughout the product. This has a positive impact on the product's performance and lifespan.
[0096] S17: Compressing the finished dry powder to obtain an initial finished product;
[0097] S18: Activate the initial finished product to obtain a finished workpiece.
[0098] Mixing and stirring promote full contact and fusion of the components. Grinding further refines the particles and increases the specific surface area. Homogenization ensures that the components are more evenly distributed. Drying and dry binder treatment form a finished dry powder with a certain strength. Compression molding gives the product a specific shape and density. Activation treatment enhances its adsorption performance and hydrogen-rich effect. This preparation method achieves efficient preparation of activated carbon hydrogen-rich sheets 1 by precisely controlling the raw material ratio, multi-step processing and final activation. This method can ensure that the product has uniform components, stable structure and excellent performance, and effectively solves the problems of uneven particle distribution and insufficient structural strength that may occur during the preparation process. In addition, the activation treatment step further improves the adsorption performance and hydrogen-rich effect of the product, so that the final product meets the expected technical requirements.
[0099] The uniformity of raw material mixing directly affects the effect of subsequent grinding and homogenization. The properties of the initial solution will affect the effect of mixing and the difficulty of the subsequent drying process. The effect of grinding and homogenization will affect the pore structure and adsorption performance of the final product. The parameters of the drying and pressing process will affect the density and strength of the product. The final activation treatment is the key to the entire preparation process, which can not only enhance the adsorption performance of the product, but also improve the hydrogen enrichment effect of the product.
[0100] A specific embodiment of this preparation method is as follows: First, select 25kg of activated carbon (iodine value 1600mg / g), 25kg of alumina (of which 15kg comes from a molecular sieve with a silicon-aluminum ratio of 900, and 10kg comes from a molecular sieve with a silicon-aluminum ratio of 1200) and 2.5kg of HPMC cellulose. Put these raw materials into a high-speed mixer and stir at a speed of 1500rpm for 25 minutes to obtain a uniform raw material mixed powder. Then, 1kg of ceramic powder is slowly added to 10L of pure water, and stirred at a speed of 500rpm for 30 minutes to obtain an initial solution. The raw material mixed powder and the initial solution are added to a planetary mixer and stirred at a speed of 800rpm for 30 minutes to obtain an initial mixed solution. Then, the initial mixed solution is ground using a horizontal sand mill, the grinding time is 2 hours, and the rotation speed is 1200rpm. The ground solution is homogenized by a high-pressure homogenizer at a pressure of 100MPa for 3 times. The homogenized mother liquor is dried using spray drying technology, with an inlet temperature of 250°C and an outlet temperature of 120°C. The dried powder is mixed with 1.5 kg of dry binder in a high-speed mixer at a speed of 2000 rpm for 10 minutes to obtain a finished dry powder. The finished dry powder is pressed under a pressure of 200 MPa to obtain an initial finished product. Finally, the initial finished product is dried at 120°C for 12 hours, and then activated at 800°C in a nitrogen atmosphere for 2 hours to obtain the final activated carbon hydrogen-rich sheet 1.
[0101] This application greatly improves the batch stability of the product through precise ratio design and effective mixing process, providing reliable guarantee for large-scale production.
[0102] The specific implementation example is as follows: In an actual production process, first select a molecular sieve with a silicon-aluminum ratio of 900, and obtain 15 kg of alumina through the molecular sieve. During the specific operation, the raw material suspension is filtered through the molecular sieve, and the filtration temperature is controlled to be 25°C, the filtration pressure is 0.1MPa, and the filtration time is 2 hours. Then select a molecular sieve with a silicon-aluminum ratio of 1200, and obtain 10 kg of alumina through the molecular sieve. During the operation, the raw material suspension is filtered through the molecular sieve, and the filtration temperature is controlled to be 30°C, the filtration pressure is 0.15MPa, and the filtration time is 1.5 hours. The two types of alumina obtained are mixed to obtain a total of 25 kg of alumina raw material. The alumina raw material obtained by this method has high purity and uniformity, and can significantly improve the performance and quality of the final activated carbon hydrogen-rich sheet 1.
[0103] Compared with the traditional method of obtaining alumina using a single molecular sieve, the technical solution proposed in this application has significant advantages. Traditional methods usually only use one molecular sieve with a silicon-aluminum ratio, which makes it difficult to balance the purity and cost of alumina. However, this application uses two molecular sieves with different silicon-aluminum ratios, which can effectively control costs while ensuring the purity of alumina. In addition, the combination of two aluminas with different properties makes the final alumina raw material have more balanced performance, which is of great significance for improving the overall performance and quality of the activated carbon hydrogen-rich sheet 1.
[0104] The mother liquor is heated to 250°C and dried using hot air. The purpose of this step is to quickly and effectively remove moisture from the mother liquor while maintaining the properties of the active ingredients. High-temperature heating can accelerate the evaporation of water, while the use of hot air can accelerate the loss of water and improve the drying efficiency. This method can ensure that the obtained mother liquor dry powder has a good degree of dryness and uniformity. Secondly, a dry binder is added to the obtained mother liquor dry powder, and dispersed and mixed by high-speed rotation. The addition of dry binders can enhance the structural stability and molding properties of the final product. The high-speed rotation dispersion mixing method can ensure that the dry binder and the mother liquor dry powder are fully and evenly mixed, avoiding local aggregation or uneven distribution, thereby ensuring the homogeneity and performance consistency of the final product.
[0105] In the process of drying the mother liquor, efficient drying can be achieved in a variety of ways. For example, a hot air circulation oven can be used to evenly spread the mother liquor on a baking tray, set the oven temperature to 250°C, and turn on the hot air circulation system. The speed of the hot air can be adjusted according to actual conditions, generally controlled between 5-10m / s. The drying time usually takes 2-4 hours, and the specific time can be determined according to the initial water content of the mother liquor and the desired final degree of drying.
[0106] Another feasible method is to use spray drying technology. The mother liquor is atomized into fine droplets through a high-pressure nozzle, and hot air at 250°C is introduced at the same time. Due to the large surface area of the droplets, they are fully in contact with the hot air, which can achieve rapid drying. This method is particularly suitable for large-scale production and can be operated continuously to improve production efficiency.
[0107] During the dry binder addition and mixing stage, a high-speed mixer can be used. First, the dried mother liquid dry powder is placed in the mixer, and then the dry binder is added according to the predetermined ratio. The speed of high-speed stirring is usually set between 1000-2000rpm, and the mixing time is generally 10-20 minutes. This high-speed stirring can break up the particle agglomeration and promote the full contact and uniform distribution of the dry binder and the mother liquid dry powder.
[0108] It is worth noting that the technical solution of the present application has a positive interaction with the formula and preparation method of the activated carbon hydrogen-rich sheet 1 in the aforementioned claims. High-temperature drying and hot air treatment help to maintain the high specific surface area and large porosity of the activated carbon, which corresponds to the high iodine value (1400-1800 mg / g) requirement of the activated carbon, and is conducive to improving the hydrogen adsorption capacity of the final product. At the same time, the uniform dispersion of the dry binder helps to give full play to the role of alumina and enhance the mechanical strength and wear resistance of the product.
[0109] The technical solution of this application has taken a series of innovative measures to solve the problem of how to effectively dry the mother liquor and obtain high-quality finished dry powder. First, high-temperature drying at 250°C can quickly remove moisture from the mother liquor, significantly shorten the drying time, and improve production efficiency. The use of hot air further accelerates the loss of water and ensures the uniformity of drying. This efficient drying method can not only maintain the characteristics of the active ingredients, but also maximize the retention of the pore structure of activated carbon and alumina, which is crucial to the performance of the hydrogen-rich sheet 1.
[0110] Secondly, the addition of dry binder and high-speed mixing steps solve the structural stability problem of the finished dry powder. Dispersed mixing by high-speed rotation ensures full contact and uniform distribution of dry binder and mother liquid dry powder. This method avoids the problem of local aggregation or uneven distribution, thereby ensuring the homogeneity and performance consistency of the final product. The evenly distributed dry binder can effectively connect the activated carbon and alumina particles, improving the mechanical strength and durability of the hydrogen-rich sheet 1.
[0111] In practical applications, the following specific embodiments can be used: 50 kg of mother liquor is placed in a hot air circulation oven, the temperature is set to 250 ° C, and the hot air speed is 8 m / s. The drying time is 3 hours, and about 25 kg of mother liquor dry powder is obtained. The dry powder is transferred to a high-speed mixer, and 1.5 kg of dry binder (such as polyvinyl alcohol) is added at a ratio of 3%. The mixer speed is set to 1500 rpm and the mixing time is 15 minutes. After this series of treatments, the finished dry powder has good fluidity and uniformity, which lays the foundation for the subsequent pressing and activation processes.
[0112] Compared with traditional natural drying at room temperature or simple hot air drying, the technical solution of the present application has significant advantages. Traditional methods often require a long drying time, which can easily lead to degradation of active ingredients or collapse of pore structures. The high-temperature rapid drying and hot air treatment adopted in this application can effectively remove moisture in a short time while retaining the original properties of activated carbon and alumina to the greatest extent. In addition, traditional methods often have problems with uneven mixing during the binder addition process, which affects the consistency of product quality. The high-speed dispersion mixing technology adopted in this application can ensure the uniform distribution of the dry binder, significantly improving the structural stability and performance consistency of the product.
[0113] Activating the initial finished product to obtain a finished workpiece includes: continuously drying the initial finished product for 12 hours at an ambient temperature of 120° C.; placing the dried finished product in an activation furnace for activation to obtain a finished workpiece.
[0114] This technical solution mainly involves two key steps: drying and activation. First, the initial finished product is continuously dried for 12 hours at an ambient temperature of 120°C. The purpose of this step is to remove moisture and other volatile substances that may exist in the initial finished product. Through long-term drying, it can be ensured that the moisture inside the product is fully removed to prepare for the subsequent activation step. Secondly, the dried finished product is placed in an activation furnace for activation. Activation is an important process that can increase the specific surface area of the product, improve its adsorption capacity and reaction activity. In the activation furnace, the activation effect may be achieved by high temperature or specific gas treatment. The combination of these two steps can effectively improve the performance of the activated carbon hydrogen-rich sheet 1. The drying step ensures the stability and uniformity of the product, while the activation step further enhances the functional characteristics of the product. In this way, a finished workpiece with excellent performance can be obtained, which meets the high quality requirements of the activated carbon hydrogen-rich sheet 1.
[0115] The drying step of the present application can be achieved in a variety of ways. In addition to continuous drying for 12 hours at an ambient temperature of 120°C, a segmented drying method can also be used. For example, first dry at 80°C for 6 hours, then heat to 120°C and continue drying for 6 hours. This segmented drying can better control the gradual removal of moisture and reduce the generation of internal stress in the product. In addition, vacuum drying can also be used, drying for 8-10 hours at a temperature of 80-100°C and a vacuum degree of -0.05 to -0.1MPa. Vacuum drying can achieve efficient drying at a lower temperature, which is beneficial to protect the structure of the product.
[0116] The activation step can also be implemented in a variety of ways. Common activation methods include physical activation and chemical activation. Physical activation is usually carried out at a high temperature of 600-900°C using gases such as water vapor or carbon dioxide, and the time can range from 30 minutes to 2 hours, depending on the product requirements. Chemical activation can use activators such as zinc chloride, phosphoric acid or potassium hydroxide at a temperature of 400-700°C, and the treatment time is usually 1-3 hours. These two methods have their own advantages and can be selected according to specific needs.
[0117] There is a close relationship between the drying and activation steps. Sufficient drying creates good conditions for subsequent activation. The moisture and volatile substances removed during the drying process provide space for the formation of new pores during the activation process. At the same time, the drying process may also have an impact on the microstructure of the product, which will be further amplified during the activation process, thus affecting the performance of the final product. Therefore, precise control of drying parameters is crucial to obtain the ideal activation effect.
[0118] The technical solution of this application not only solves the problem of moisture and volatiles in the initial finished product through the organic combination of drying and activation, but also significantly improves the specific surface area and adsorption capacity of the product. During the drying process, the temperature of 120°C and the duration of 12 hours ensure the full removal of moisture while avoiding the structural damage that may be caused by excessive temperature. The activation process further optimizes the pore structure of the product and enhances its adsorption and catalytic properties. Compared with simple drying or activation, this treatment method can improve product performance more comprehensively, so that the final finished workpiece performs well in water purification and hydrogen generation.
[0119] In addition, the embodiments of the present invention are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. An activated carbon hydrogen-rich sheet, characterized in that: The activated carbon hydrogen-rich sheet is configured based on activated carbon, alumina, cellulose, a release agent and a dry binder; The activated carbon hydrogen-rich sheet has the following ingredients: 50 parts of activated carbon, 50 parts of aluminum oxide, 5 parts of cellulose, 1 part of a release agent and 3 parts of a dry binder.
2. The activated carbon hydrogen-rich sheet according to claim 1, characterized in that: The iodine value of the activated carbon is H, and the value range of H is: 1400 mg / g≤H≤1800 mg / g.
3. The activated carbon hydrogen-rich sheet according to claim 1, characterized in that: The cellulose is HPMC cellulose.
4. The activated carbon hydrogen-rich sheet according to claim 1, characterized in that: The release agent is a polyether substance.
5. A method for preparing an activated carbon hydrogen-rich sheet, characterized in that: The preparation method is used to prepare the activated carbon hydrogen-rich sheet as claimed in any one of claims 1 to 4; The preparation method comprises: Selecting a plurality of raw material components according to the proportion, and mixing the plurality of raw material components uniformly to obtain a raw material mixed powder; Dissolving a preset amount of ceramic in pure water to obtain an initial solution; Mixing the raw material mixed powder and the initial solution, and stirring for a first preset time to obtain an initial mixed solution; Grinding the initial mixed solution by a grinding machine; homogenizing the initial mixed solution after the grinding process to obtain a mother solution; After drying the mother liquor, a finished dry powder is obtained based on a dry binder treatment; The finished dry powder is compressed to obtain an initial finished product; The initial finished product is activated to obtain a finished workpiece.
6. The method for preparing an activated carbon hydrogen-rich sheet according to claim 5, characterized in that: The method of selecting a plurality of raw material components according to the proportion and uniformly mixing the plurality of raw material components to obtain the raw material mixed powder includes: 25 kg of activated carbon, 25 kg of aluminum oxide and 2.5 kg of cellulose were selected, and the activated carbon, the aluminum oxide and the cellulose were stirred and mixed to obtain a raw material mixed powder.
7. The method for preparing an activated carbon hydrogen-rich sheet according to claim 6, characterized in that: The operation of obtaining 25 kg of alumina includes: Obtain 15 kg of alumina through a molecular sieve with a silicon-aluminum ratio greater than 800; 10 kg of alumina was obtained by passing through a molecular sieve having a silicon-aluminum ratio of 1200.
8. The method for preparing an activated carbon hydrogen-rich sheet according to claim 5, characterized in that: The step of mixing the raw material mixed powder and the initial solution and stirring for a first preset time to obtain the initial mixed solution comprises: The raw material mixed powder and the initial solution are mixed, and the raw material mixed powder and the initial solution are continuously stirred for 30 minutes by a stirrer.
9. The method for preparing an activated carbon hydrogen-rich sheet according to claim 5, characterized in that: After the mother liquor is dried, the finished dry powder is obtained based on the dry binder treatment, which comprises: The mother liquor is heated to 250° C., and the heated mother liquor is dried by hot air to obtain a mother liquor dry powder; Add dry binder to the mother liquid dry powder and disperse and mix by high-speed rotation.
10. The method for preparing an activated carbon hydrogen-rich sheet according to claim 5, characterized in that: The activation of the initial finished product to obtain the finished workpiece comprises: The initial finished product was dried continuously for 12 hours at an ambient temperature of 120°C; The dried finished product is placed in an activation furnace for activation to obtain a finished workpiece.
Citation Information
Patent Citations
Apparatus for hydrogenating biocompatible solution
CN102741172A
Preparation method of micro-electrolysis magnesium-based ceramic material
CN112897987A
Green coupling hydrogen production system and method
CN115845759A
Seawater desalination reduced water generating water purification system
KR1020140004481A
Combined water filtration system for enhancing drinking water properties for human health
US20220073397A1